TINGKAT KESEJAHTERAAN KELUARGA DAN KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR - Vivi Ibriyanti; Taufik Taufik (Herodotus: Jurnal Pendidikan IPS, 2019)
The purpose of this study is to find out: 1) The influence of the level of Family Welfare and Emotional Intelligence together on the Social Science Learning Achievement of State Junior High School students in Tangerang Regency. 2) The Effect of Family Welfare Level on Social Science Learning Achievement of State Junior High School students in Tangerang Regency. 3) The Effect of Emotional Intelligence on Social Science Learning Achievement of State Junior High School students in Tangerang Regency. The method used in this study is a survey method with correlation and regression analysis techniques. The population of this research was VIII grade students of SMP Negeri 1 Jayanti, Tangerang Regency, SMP Negeri 2 Jayanti, Tangerang Regency, and SMP Negeri 1 Balaraja, Tangerang Regency, totaling 600 students. The sample in this study amounted to 80 students. The results showed that: 1) This is evidenced by the acquisition of Sig. 0,000 <0.05 and Fcount = 35.208. 2) This is evidenced by the acquisition of Sig. 0,000 <0.05 and tcount = 3,713. 3) This is evidenced by the acquisition of Sig. 0,000 <0.05 and tcount = 3.959.